Knowledge on drug abuse among MBBS first year students of Chitwan Medical College - Paudel, Gita; Chaurasia, Lokeshwar; Bhurtyal, Karma Murti; Karki, Sirisa (Journal of Chitwan Medical College, 2021)
Background: Currently, drug abuse is booming in developing countries including Nepal, which may directly affect personal as well as socioeconomic condition of individual and community. Teenage, being the most crucial stage of life, is the age when teenagers want to explore a lot of things and is curious about new experiments. So, they think that, drugs assist them to overcome all the problems they face in day to day life. Therefore, the aim of this study was to assess the knowledge regarding drug abuse among MBBS first year students of Chitwan Medical College. Methods: A cross-sectional study was carried out to determine the knowledge regarding drug abuse among MBBS first year students of CMC. A self-administered questionnaire was used to collect information, which was adopted from previous studies. Study participants were briefed about the nature of the study and the procedure of completing the questionnaire was explained. After completion of the questionnaire, data was collected, reviewed, organized and expressed as counts/percentages and statically analyzed using SPSS version 20. Results: The current study showed that, majority 81.3% of the participants had satisfactory whereas 18.8% of the participants had unsatisfactory level of knowledge about drug abuse. Conclusions: Majority of the MBBS first year students had satisfactory knowledge regarding drug abuse and only few had unsatisfactory knowledge. So, for them it is deemed necessary to update their knowledge regarding drug abuse, as it is one of the crucial matters of concern these days.